Primerjava pravic, dolžnosti in pravnih položajev partnerjev istega in različnega spola v Republiki Sloveniji - Rajgelj, Barbara (Podjetje in delo, 2016)
In this article, the author analyses the rights, duties and legal positions of partners of the same and different sexes in the Slovenian law. The analysis is designed as a chronological review of 30 years' gradual development of the legal management of same-sex partnerships in Slovenia with the emphasis on an in-depth analysis of differentiation between same-sex and different sex partnerships, introduced with the Same-Sex Partnership Registration Act. Since its introduction in 2005, the differences were gradually reduced, but will mostly be entirely removed with the new Partnership Act, which is already in force and comes into use in February 2017. The challenge for the future, most likely also for constitutional legal judgement, remains mostly in the field of relations towards children, that is, the justification of procedures with biomedical aid and joint adoption, which, according to the Partnerships Act, are still excluded for same sex partners.
Keywords: človekove pravice; družinsko pravo; istospolna partnerska skupnost; partnerstvo; pravna ureditev; Slovenija; zakonska zveza